Respon Pemberian Multi Mineral Blok (MMB) Terhadap Pertambahan Bobot Badan Sapi Bali - Farizal, Farizal (Fakultas Peternakan Universitas Jambi, 2008)
The objective of the study was to observe response of feeding Bali cattle multi mineral block (MMB) as a feed supplement on the body weight gain of Bali cattle. Nine male Bali cattle aged between 1 – 1,5 years were allotted in the Randomized Block Design consisted of 3 treatments and 3 blocks of body weight. Parameters measured were roughage intake, absolute and relative body weight and feed efficiency. .Result of this experiment shows that feeding MMB has influence ( P < 0,05 ) on roughage intake and body weight gain ( P < 0,01 ). Duncan multiple range test shows that body weight gain of cattle feed treatment R 1 and R 2 was high than those had treatment R0. It can be concluded that feeding MMB as a supplement could increase body weight gain of Bali Cattle.